Application of Tegeran (Maclura cochinchinensis) bark as natural tanning agent for the quality of tilapia fish skin - Gresy Griyanitasari; Iwan Fajar Pahlawan; Umi Reza Lestari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2019)
Chrome is a tanning material that is very harmful to the environment hence its role is being replaced with vegetable tanning materials. One of the natural ingredients that contain tannin is Tegeran (M. cochinchinensis) wood. The aim of this study was to determine the effect of M. cochinchinensis as natural tanning agent for tilapia fish skin. Tannin contained in the M. cochinchinensis was being extracted using three solvents: water, ethanol, and water-ethanol (1:1). The composition of the material and the solvent was 1:4. It was heated in the waterbath at temperature 70 °C for 3 hours. The results showed that the use of M. cochinchinensis as natural tanning agent could at once gave unique color to the tanned fish skin. The average of shrinkage temperature was 78.11°C. Leather tanned with M. cochinchinensis that was extracted with water showed higher value of tensile strength and tear strength than those with ethanol and water-ethanol.